Considerations for the development of cost‐effective cell culture media for cultivated meat production. Issue 1 (5th December 2020) - O'Neill, Edward N.; Cosenza, Zachary A.; Baar, Keith; Block, David E.
Abstract: Innovation in cultivated meat development has been rapidly accelerating in recent years because it holds the potential to help attenuate issues facing production of dietary protein for a growing world population. There are technical obstacles still hindering large‐scale commercialization of cultivated meat, of which many are related to the media that are used to culture the muscle, fat, and connective tissue cells. While animal cell culture media has been used and refined for roughly a century, it has not been specifically designed with the requirements of cultivated meat in mind. Perhaps the most common industrial use of animal cell culture is currently the production of therapeutic monoclonal antibodies, which sell for orders of magnitude more than meat. Successful production of cultivated meat requires media that is food grade with minimal cost, can regulate large‐scale cell proliferation and differentiation, has acceptable sensory qualities, and is animal ingredient‐free. Much insight into strategies for achieving media formulations with these qualities can be obtained from knowledge of conventional culture media applications and from the metabolic pathways involved in myogenesis and protein synthesis. In addition, application of principles used to optimize media for large‐scale microbial fermentation processes producing lower value commodity chemicals and food ingredients can also be instructive. As such, the present review shall provide an overview of the current understanding of cell culture media as it relates to cultivated meat.